Chemical Cleaning of Fouled Polyethersulphone Nanofiltration Membranes with Ethylenediaminetetraacetic Acid (Journal of Applied Membrane Science & Technology, 2018)
This study mainly investigated the potential use of ethylenediaminetetraacetic acid (EDTA) as the chemical cleaning agent to restore the permeate flux of organically fouled polyethersulfone (PES) nanofiltration (NF) membranes under varying applied pressures. The cleaning efficiency was quantified based on flux recovery rate. The results showed that the optimum EDTA concentration is 1.0 wt%, within the range investigated, which proved that higher concentration does not necessary enhance the cleaning efficiency. The results also demonstrated that the highest flux recovery was achieved at the applied pressure of 14 bar regardless of EDTA concentration. Overall, the maximum flux recovery that could be achieved is only 35.03%, implying EDTA is not very effective in removing foulants from the PES NF membranes.